Significant Within-Individual Variability in VCTE Liver Stiffness Measurements at Two Intercostal Spaces in Subjects with MASLD: Implications for Evaluating Improvement in Liver Fibrosis After Weight-Loss or Liver-Directed Therapy - Jordan S. Woodard; Jena Velji-Ibrahim; Gary A. Abrams (Diseases)
Introduction: Studies have compared the group-averages of liver stiffness measures (LSMs) from multiple rib spaces by vibration-controlled transient elastography (VCTE) to stage liver fibrosis. No previous study has assessed within-individual liver stiffness variation from two rib spaces in individuals with metabolic-dysfunction associated steatotic liver disease (MASLD). Methods: We evaluated within-individual LSM variation according to body weight classification and its clinical implication. From October 2019 to March 2024, VCTE was performed on MASLD patients or those at high risk, in accordance with FibroScan guidelines. The LSMs were categorized into stages: <5 kPa (stage 0), 5–7.99 kPa (stage 1), 8–9.99 kPa (stage 2), 10–13.99 kPa (stage 3), and 14+ kPa (stage 4). Measurements with 10 values and IQR/median ≤ 0.30 were included, using SPSS V25.0 for analysis. Results: Among 1107 subjects (age 54.4 ± 13.9 years, 56.9% female), 7.7% were normal weight, 20.7% overweight, 28.9% class 1 obesity, 21.3% class 2 obesity, and 21.2% class 3 obesity. Significant within-individual variation was noted: 67% (0–2 kPa) variation, 23.4% (2.1–6 kPa), and 10% (≥6.1 kPa). Class 3 obese individuals had the maximum variation. Comparing the group-average of LSM at each ICS site showed that 95% of individuals were within one fibrosis stage. Conclusions: While LSM group-averages at different rib sites provides reliable fibrosis staging, significant within-individual variability exists especially in class 3 obesity. This should be considered when serial LSM assessments are used to assess medical therapeutic efficacy.